Naiads (Bivalvia - Hyriidae) in the "Conglomerado osifero" (late Miocene), Entre Rios Province, Argentina - Pérez, Leandro Martín (2022)
The freshwater mussels of the family Hyriidae (Bivalvia) are widespread in the Neotropical region, including several fossil and living species of the genus Diplodon Spix. A specimen assigned to Diplodon sp., recovered from the "Conglomerado osífero" (late Miocene) at La Toma Vieja, north of Paraná City (Entre Ríos Province, Argentina), is described herein. The report of Diplodon sp. in the "Conglomerado osífero" would support the traditional interpretation of a fluvial paleoenvironment for this horizon. This is the first accurate fossil record of the genus for the Entre Ríos Province, extending the occurrence of the family Hyriidae to the late Miocene of the Mesopotamian region.